2016
DOI: 10.1002/bit.26048
|View full text |Cite
|
Sign up to set email alerts
|

Toward “homolactic” fermentation of glucose and xylose by engineered Saccharomyces cerevisiae harboring a kinetically efficient l‐lactate dehydrogenase within pdc1pdc5 deletion background

Abstract: l-Lactic acid is an important platform chemical and its production from the lignocellulosic sugars glucose and xylose is, therefore, of high interest. Tolerance to low pH and a generally high robustness make Saccharomyces cerevisiae a promising host for l-lactic acid fermentation but strain development for effective utilization of both sugars is an unsolved problem. The herein used S. cerevisiae strain IBB10B05 incorporates a NADH-dependent pathway for oxidoreductive xylose assimilation within CEN.PK113-7D bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…A dependency of both Y LA and lactic acid productivity (Q LA ) on oxygen supply by aeration was also noted in a recent study from the current authors, in which two strains of S. cerevisiae , IBB14LA1 and IBB14LA1_5, producing lactic acid from xylose were presented [ 20 ]. Both these strains are descendants of strain IBB10B05, which harbors a XR/XDH pathway engineered for redox-neutral assimilation of xylose and has furthermore undergone evolution for accelerated xylose-to-ethanol fermentation [ 28 , 29 ].…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…A dependency of both Y LA and lactic acid productivity (Q LA ) on oxygen supply by aeration was also noted in a recent study from the current authors, in which two strains of S. cerevisiae , IBB14LA1 and IBB14LA1_5, producing lactic acid from xylose were presented [ 20 ]. Both these strains are descendants of strain IBB10B05, which harbors a XR/XDH pathway engineered for redox-neutral assimilation of xylose and has furthermore undergone evolution for accelerated xylose-to-ethanol fermentation [ 28 , 29 ].…”
Section: Introductionsupporting
confidence: 67%
“…To channel the metabolic flux away from ethanol towards lactic acid production, further engineering strategies were applied. These included (a) the alleviation or disruption of the ethanol pathway by gene deletion of pdc1 , pdc5 , pdc6 , adh1 , or a combination thereof [ 9 , 10 , 12 , 16 ]; (b) the optimization of ldh gene expression [ 11 , 17 , 18 ], (c) the application of LDHs with high catalytic activities [ 19 , 20 ]; (d) the perturbation of the intracellular redox balance to increase the availability of NADH for the LDH-catalyzed reaction [ 18 ]; (e) the reduction of by-product formation by disruption of the glycerol pathway [ 21 ], and (f) the reduction of ATP consumption by replacing the native with an ATP-independent pathway for acetyl-CoA production from acetaldehyde [ 15 , 22 ]. Recent studies by us [ 20 ] and others [ 23 ] further showed that xylose-to-lactic acid conversion in S. cerevisiae is possible, representing an important step to advance lignocellulose-to-lactic acid processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…S ynthetic biology and metabolic engineering approaches have been used successfully to produce a wide range of value-added products (1)(2)(3)(4)(5)(6)(7)(8). Most efforts in biosynthesis have focused on the establishment and optimization of metabolic fluxes toward the targeted product in the cytoplasm, before excretion or extraction (9)(10)(11)(12). The product line of available biocatalysts is limited by current strategies, especially when the targeted compound is structurally similar to other metabolites, which complicates the downstream processes for purification.…”
mentioning
confidence: 99%